Catalytic Hypervalent Iodine Promoters Lead to Styrene Dimerization and the Formation of Tri- and Tetrasubstituted Cyclobutanes - Donohoe, T; Colomer, I; Coura Barcelos, R (Wiley, 2016)
We report that the use of catalytic quantities of hypervalent iodine reagents (PIDA or Dess Martin Periodinane) allows the rapid and stereoselective formation of cyclobutanes under very mild conditions. The presence of a fluorinated solvent is essential for the success of these reactions which are able to form unsymmetrical tri- and tetrasubstituted cyclobutanes via a heterodimerisation process involving two different alkenes.